Stanniocalcin 1 effects on the renal gluconeogenesis pathway in rat and fish - Schein, Vanessa (2018)
The mammalian kidney contributes significantly to glucose homeostasis through gluconeogenesis. Considering that stanniocalcin 1 (STC1) regulates ATP production, is synthesized and acts in different cell types of the nephron, the present study hypothesized that STC1 may be implicated in the regulation of gluconeogenesis in the vertebrate kidney. Human STC1 strongly reduced gluconeogenesis from C-14-glutamine in rat renal medulla (MD) slices but not in renal cortex (CX), nor from C-14-lactic acid. Total PEPCK activity was markedly reduced by hSTC1 in MD but not in CX. Pck2 (mitochondrial PEPCK isoform) was down-regulated by hSTC1 in MD but not in CX. In fish (Dicentrarchus labrax) kidney slices, both STC1-A and -B isoforms decreased gluconeogenesis from C-14-acid lactic, while STC1-A increased gluconeogenesis from C-14-glutamine. Overall, our results demonstrate a role for STC1 in the control of glucose synthesis via renal gluconeogenesis in mammals and suggest that it may have a similar role in teleost fishes. (C) 2015 Elsevier Ireland Ltd. All rights reserved.